Isolation and Identification of Actinomycetes with Antibacterial Activity from Soil Samples Around Kandy, Sri Lanka - Navoda Bandara; Tennakoon T.M.I.U.K (Current Research in Pharmaceutical Sciences, 2023)
Commercially exploited antibiotics are originally isolated from Actinomycetes.  Even so, Actinomycetes are mostly underestimated for their antibacterial potential. This study aimed to isolate and identify Actinomycetes with antibacterial activity from soil samples around Kandy Sri Lanka. Soils were taken from five different habitats (waste disposal (WS), originally cultivated (OR), riverbanks (RB), pasture (PS), and rhizospheric (RH)). Serially diluted samples were grown on an Actinomycetes isolation agar medium and screened for antibacterial activity against Escherichia coli (ATCC25922), Staphylococcus aureus (ATCC25923), Pseudomonas aeruginosa (ATCC27853) and Klebsiella pneumoniae (ATCC13883) using perpendicular streak method. Isolates with inhibitory activity were subjected to secondary screening. 19 actinomycetes isolates were identified of which 10 isolates showed inhibitory activity during preliminary screening.  During the secondary screening, two isolates from RB site and one isolate from OR site expressed broad-spectrum antibacterial activity while the other five isolates from RB, OR, WS, and PS sites inhibited either Escherichia coli or Staphylococcus aureus. The soil samples are a promising source of novel antibacterial compounds and thus these findings can be used for further investigations in developing broad-spectrum antibiotics for therapeutic targets in the future.